Interaction and language directed at children aged 15 months (Psicologia USP, 2017)
In this study we compare maternal and paternal interaction and speech directed to their children, in order to analyze differences and similitudes between the dyads. For that purpose, 80 dyads were taped in a free play situation - forty 15 months old children (25 girls, 15 boys) interacting with their parents. Results demonstrate no significant differences regarding the way mothers and fathers interact with their sons and daughters. However, differences in mothers versus fathers’ style of communication toward their children were found, particularly naming and positive evaluation behaviors. Although differences were found, we underline positive correlation in interaction and communication of cohabiting parents.